Verdensmestre i tværsektorielle overgange eller lost in translation? - Sine Lehn; Karin Højbjerg; Cathrine Sand Nielsen; Elise Bromann Bukhave (Tidsskrift for Professionsstudier)
The article examines the implications of a national revision of bachelor's degree programmes in healthcare that aimed to increase students' competencies for cross-sectoral collaboration. Through critical policy analysis inspired by Nudzor's approach to policy as text and discourse, the article provides insight into the complex dynamics underlying the policy-practice gap related to this particular learning objective. The analysis shows that the introduction of this standardised learning outcome across bachelor's degree programmes in the health field has created challenges in clinical educational practice. While some programmes can relatively easily 'translate' policy into educational practice, others struggle to create meaningful and realisable educational practice with a focus on cross-sectoral competence development. Policy thus produces differentiations in the educational field. Some programmes and implementation actors are positioned as 'good', while others are left in less favourable positions. The article highlights the importance of illuminating how policy resonates with and influences practice in a complex and differentiated way. Furthermore, the article points to the need to critically discuss the transformation of objectives of health system policy to objectives of professional competencies.